Phytochemical Compounds of Ethanol Extract Kigelia africana (Lam.) Benth. from Pericarpium, Fructus, and Semen using LCMS/MS and in Silico Study (Potential of Phosphodiesterase-5 Inhibitor) - Rizka Putra Samudra; Sukardiman Sukardiman; Retno Widyowati (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Erectile dysfunction can be treated by pharmacological therapy with phosphodiesterase-5 inhibitors (PDE5-I). One plant that has a function as a phosphodiesterase-5 inhibitor is Kigelia africana (Lam.) Benth. Research on Kigelia africana (Lam.) Benth. An extract as a Phosphodiesterase type 5 (PDE 5) inhibitor is still lacking. This research aims to determine the phytochemical compounds in the 70% ethanol extract of the pericarpium, fructus and semen of Kigelia africana (Lam.) Benth. with LC-MS/MS and to determine the ligand-protein interaction through in-silico studies. In previous studies, no one compared each part of the Kigelia africana (Lam.) Benth. as an aphrodisiac. The results of the identification of the 70% ethanol extract of Kigelia africana (Lam.) Benth. found several alkaloids, flavonoids, iridoids, phenolics, polyphenols, coumarins, steroids and fatty acids. Based on the results of molecular docking on 70% ethanol extract of pericarpium, fructus and semen of Kigelia africana (Lam.) Benth., 18 compounds, 20 compounds and 18 compounds were obtained sequentially, which were analyzed using LC-MS/MS. The sitosterol compound with (∆G = -8.90 kcal/mol) was identified in the three parts of the 70% ethanol extract sample of kunto bimo fruit, which showed the highest affinity for binding to the target protein compared to sildenafil with (∆G = -8.68 kcal/mol). Sitosterol compound has the same amino acid residues as the native ligand, namely ILE A:824, TYR A:664, ALA A:779, ILE A:768, ALA A:767, LEU A:765, ASN A:661, HIS A:613, PHE A:786, VAL A:782, LEU A:804, MET A:816, PHE A:820 in hydrophobic bonds. Phytochemical compounds from Kigelia africana (Lam.) Benth. It has the potential as an alternative additional therapy and a promising source for the discovery of new drugs as aphrodisiacs targeting PDE5.